Insurance density and the digital economic development: a China perspective. Issue 2 (10th July 2023) - Chen, Xiao Hui; Zhang, Li
Abstract: The digital economy is an important starting point for China's high-quality economic development, and insurance density is a key variable for measuring the development of the insurance industry. Can increasing insurance density promote digital economic development? Based on China's provincial digital economic development index from 2013 to 2021, this study explores this question. The results show that a positive U-shaped nonlinear relationship between insurance density and digital economy, and there is an inflection point in insurance density. When insurance density is lower than the inflection point, an increase in insurance density will inhibit digital economic development; when it exceeds the inflection point, a further increase in insurance density will promote digital economic development. Furthermore, there is a positive U-shaped nonlinear relationship between insurance density and traditional technological innovation, which is conducive to digital economic development. As such, insurance density affects digital economic development through the transmission of traditional technological innovation. The findings have reference significance for developing countries to improve their insurance penetration rate and develop their digital economy to promote economic development.